Cosmology of Native Indonesian Religions in Facing Contemporary Times: A Study of Sundanese Javanese Religion - Alfan, Muhammad; Muhyiddin, Asep; Thohir, Ajid (Hanifiya: Jurnal Studi Agama-Agama, 2024)
The reality of modernity, which has given rise to various complexities that are sometimes detrimental to humanity, has revived local religions which indeed have their own cosmology, which is seen as saving the world. The main focus of the research is cosmology within the teachings of Agama Sunda Djawa, exploring sources of ethics, views on the afterlife, and environmental ethics. The Seren Taun ceremony, as part of local cultural wisdom, becomes the center of attention in understanding the meaning of rituals and the symbolic significance of the Paseban building. This research utilizes a qualitative method with a phenomenological approach, involving informants such as followers of Madraism, Agama Djawa Sunda (ADS; the Sundanese Javanese Religion), Paguyuban Adat Cara Karuhun Urang, and Adat Karuhun Urang. The results provide a deep understanding of the administrative and discriminatory challenges faced by Sunda Wiwitan followers and their efforts to maintain their existence and beliefs. This research also reveals the relationship between traditional arts, especially Gemyung art, with the expression of Sundanese cosmology. Overall, this research contributes to the understanding of religion and spirituality in Indonesia while also highlighting social, political, and administrative issues faced by certain religious groups.